Efectos de una biopelícula con aceites esenciales de naranja y eucalipto en el crecimiento de hongos de la malanga de exportación - Marcillo Molina, Raissa Lisette (2021)
The present work was carried out at the Tropicalexpor packing plant, located in Santo Domingo de los Tsáchilas, with the objective of evaluating the effects of a biofilm with essential oils of orange and eucalyptus on the growth of taro fungi for export. The process began with obtaining taro starch with which the biofilm was made with essential oils of orange and eucalyptus in doses of 0.2%, 0.3% and 0.4%. The microbiological analyzes of the presence or absence of fungi in export taro were carried out in the ESPAM MFL microbiology laboratory for a period of five weeks using the plate count technique by deep seeding with the NTE INEN 1529-10 standard: 2013. The experiment was conducted with a 2x3 factorial arrangement in a completely randomized design, with six treatments and three replications; the results were analyzed using the binary logistic regression statistical technique using the IBM SPSS 28 free version statistical software, which indicated that there is a significant difference between the treatments under study, all of which reduce the growth of fungi, although the results are highly variable, however, it was observed that the best treatment was that of eucalyptus essential oil with a dose of 0.4%, because it is the one that presented the highest capacity to inhibit fungi, in relation to the other concentrations, with a percentage of inhibition at the end of the 5 weeks of 83.87% taking as reference the initial microbial load.